Adhesion of germlings of Botrytis cinerea. - Doss, R P (1995)
Adhesion of conidia and germlings of the facultative plant parasite Botrytis cinerea occurs in two distinct stages. The first stage, which occurs immediately upon hydration of conidia and is characterized by relatively weak adhesive forces, appears to involve hydrophobic interactions (R. P. Doss, S. W. Potter, G. A. Chastagner, and J. K. Christian, Appl. Environ. Microbiol. 59:1786-1791, 1993). The second stage of adhesion, delayed adhesion, occurs after viable conidia have been incubated for several hours under conditions that promote germination. At this time, the germlings attach strongly to either hydrophobic or hydrophilic substrata. Delayed adhesion involves secretion of an ensheating film that remains attached to the substratum upon physical removal of the germlings. This fungal sheath, which can be visualized by using interference-contrast light microscopy, scanning electron microscopy, or atomic force microscopy, is 25 to 60 nm thick in the region immediately adjacent to the germ tubes. Germlings are resistant to removal by boiling or by treatment with a number of hydrolytic enzymes, 2.0 M periodic acid, or 1.0 M sulfuric acid. They are readily removed by brief exposure to 1.25 N NaOH. A base-soluble material that adheres to culture flask walls in short-term liquid cultures of B. cinerea is composed of glucose (about 30%), galactosamine (about 3%), and protein (30 to 44%).